Comparison of cerebral ventricular volumes and cortical thicknesses in normal rats and Genetic Absence Epilepsy (GAERS): A developmental study. Issue 68 (August 2018) - Kirazlı, Özlem; Bay, Hüsniye Hacıoğlu; Çakmak, Yusuf Özgür; Onat, Filiz; Çavdar, Safiye
Highlights: The ventricular volumes (LV and 3V) showed no statistically significant difference between Wistar and GAERS animals. GAERS animals at P60 and P30 of the MCx, P30 of the SSCx, P20 of the VCx and AuCx showed a significantly thinner cortical thickness. Thinner cortical and striatal thicknesses and smaller brain size in GAERS animals may be related to the mechanism of epileptogenicity. Abstract: Ventricular enlargement and cortical atrophy have been associated with various central nervous system diseases. The aim of the present study was to measure the volumes of the lateral (LV) and third (3V) ventricles and to determine the cortical thickness for the motor (MCx), somatosensory (SSCx), visual (VCx) and auditory (AuCx) cortex and the striatum of Wistar rats, in a developmental series at 10, 20, 30, and 60 days postnatal, and to compare them with similar data from genetic absence epilepsy rats from Strasbourg (GAERS). Serial sections were taken from the brains of Wistar and GAERS animals and were Nissl stained. Photographs were taken from specific sections of the brain for measurements of ventricular volume, cortical and striatal thickness. The image-j computer program was used for the volume and thickness measurements. The data was statistically analyzed by 3-way ANOVA using SPSS 15. Comparison of the measurements of GAERS and Wistar animals showed no statistically significant differences at any of the developmental stages regarding the ventricular (LV and 3V) volumes. However, at P60 and P30 of the MCx, P30 of the SSCx, P20 of the VCx and AuCx showed a significantly thinner cortical thickness in the GAERS than in the Wistar animals. The striatal measurements showed significant decrease in thickness of the striatum at P30 and P60. Further, brain size measurements (between the two temporal poles) showed significant decrease in the size at P30 and P60 of GAERS animals. The presence of thinner cortical and striatal thicknesses and smaller brain size in GAERS animals may suggests that these changes could be involved in the mechanism of epileptogenicity or be a result of the epileptogenicity.